THE INFLUENCE OF INCREASED CARBONATED BEVERAGES CONSUMPTION ON THE RISK OF NEPHROLITHIASIS DEVELOPMENT: A SYSTEMATIC REVIEW AND META-ANALYSIS OF OBSERVATIONAL STUDIES - Otu, Omeiza Muhammedjamiu; Doguwa, S. I.; Sa’id, Umar Yunusa; Zakari, Y. (FUDMA JOURNAL OF SCIENCES, 2025)
Nephrolithiasis, a frequent medical disorder, is affected by a variety of environmental factors, including food. Fluid consumption is an important dietary strategy for reducing kidney stone risk since it has a direct impact on nephrolithiasis. The primary goal of this study is to collect accurate and trustworthy data about the effect of carbonated beverages on the risk of developing nephrolithiasis in order to make evidence-based recommendations. To accomplish this purpose, we conducted a thorough and systematic review, followed by a meta-analysis. This enabled us to assess the link between increasing carbonated beverage consumption and nephrolithiasis risk. Our search included Medline, Web of Science, and PubMed databases up to April 2024, yielding 249 articles initially, 39 of which met eligibility requirements after title and abstract screening. The meta-analysis includes a total of 16 publications. A random-effects model was used to analyse the acquired data in order to account for differences in study design and population. We used the R programming language (version 4.3.1) to compute pooled relative risks (RRs) and 95% confidence intervals (CIs), as well as to quantitatively analyse heterogeneity using the I2 statistic. Our findings revealed a significant link between increasing carbonated beverage consumption and an increased risk of developing nephrolithiasis (RR: 1.855; 95% CI, 1.26–2.74). To reduce potential health hazards, we highly advise consumers to limit the intake of carbonated beverages. This reduction is crucial not only for minimising kidney problems and other chronic illnesses, but also for promoting nephrolithiasis prevention and encouraging people to adopt healthy eating...